Гендерні особливості професійного становлення особистості студента - Мілорадова, Наталя Едуардівна; Мовмига, Наталія Євгенівна (НТУ "ХПІ", 2015)
У статті досліджуються гендерні особливості професійного становлення особистості студента, що супроводжується зміною уявлень індивіда про себе і своє місце у соціальному світі і світі професій. Гендер надає соціально рольовий статус особистості, який визначає можливості в освіті, професійній діяльності, суспільному виробництві. У зв'язку з цим важливим аспектом стає вивчення професійного становлення з позиції гендерного підходу, коли в центрі уваги стає учень і його особистісні особливості.

The author investigates gender features of the professional development of a student, which are followed up by the changes in self-viewpoint and the place in the society. Gender is one of the basic dimensions of the social structure which comprises a social system alongside with other soсial and cultural features (race, age etc). Gender gives social and role status to a person. Such status defines possibilities in the professional activity and social relationships. All this makes the gender-based view an important aspect in the process of research of such category as professional development. This process is based upon the approach that a student and his/her personal features are in are in the main focus. Nowadays, we witness how gender roles are diminished; gender stereotypes are destroyed. This fact is proved by the number of national and foreign scientists. The process of professional development can become more efficient if gender approach is used. The proactive pedagogical assistance has to be in place. Authors underline that career preferences depend on gender characteristics.
Gender features of the professional development of student
Keywords: вища освіта; професійне становлення; гендерні особливості; гендер; студенти; gender; gender features; professional development of students